A relação dos valores pessoais e das competências profissionais dos gestores e jovens trabalhadores: um recorte das escolas municipais da Zona leste de Manaus, na Amazônia - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Considering development of school environment in the 21st century it becomes essential to work from the perspective of personal values and professional skills individuals may acquire, most of all concerning young workers and school principals who are able to convey such values and skills effectively. As a research problem for this thesis an inquiry was made to investigate how young workers’ personal values and professional skills are related to those of their school principals. In light of such discussion the main objective of this thesis was outlined as ‘an analysis of relations between school principals and young workers’ personal values and professional skills in public East Manaus municipal schools.’ In pursuit of that objective first an exploratory-descriptive survey was performed based on the theoretical fundamentals pertaining to the discussion. Subsequently a survey instrument was submitted, an online form to be completed by school principals and young workers from East Manaus municipal schools. The data was organized by means of PER matrix which yielded an output through a hybrid method (qualitative-quantitative) showing evidence of direct relationship in 100% of 19 personal values and 100% of 5 professional skills elements. The main conclusion of this thesis is that school principals convey personal values and professionals skills to young workers among their school staff.
Keywords: Escolas municipais - Manaus (AM); Escolas públicas - Organização e administração - Manaus (AM); Escola Pública - Manaus (AM); CIÊNCIAS HUMANAS; Gestão Escolar; Amazônia; Zona Leste de Manaus; Matriz Modelo; SEMED Manaus